2015
DOI: 10.1186/s12931-015-0233-3
|View full text |Cite|
|
Sign up to set email alerts
|

A flavanone from Baccharis retusa (Asteraceae) prevents elastase-induced emphysema in mice by regulating NF-κB, oxidative stress and metalloproteinases

Abstract: BackgroundPulmonary emphysema is characterized by irreversible airflow obstruction, inflammation, oxidative stress imbalance and lung remodeling, resulting in reduced lung function and a lower quality of life. Flavonoids are plant compounds with potential anti-inflammatory and antioxidant effects that have been used in folk medicine. Our aim was to determine whether treatment with sakuranetin, a flavonoid extracted from the aerial parts of Baccharis retusa, interferes with the development of lung emphysema.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 44 publications
(67 reference statements)
1
40
0
3
Order By: Relevance
“…In the sakuranetin-treated emphysematous animals, reductions in lung inflammation, which were associated with attenuated lung parenchymal remodeling and in alveolar destruction, were observed. Sakuranetin treatment reduced lung inflammation and pro-inflammatory cytokine levels (M-CSF, TNF-α, IL-1β, MCP-1 and MIP-2) in lung homogenates [77].…”
Section: Antiinflammatory Activitymentioning
confidence: 92%
“…In the sakuranetin-treated emphysematous animals, reductions in lung inflammation, which were associated with attenuated lung parenchymal remodeling and in alveolar destruction, were observed. Sakuranetin treatment reduced lung inflammation and pro-inflammatory cytokine levels (M-CSF, TNF-α, IL-1β, MCP-1 and MIP-2) in lung homogenates [77].…”
Section: Antiinflammatory Activitymentioning
confidence: 92%
“…Under this condition, sakuranetin reduced the NF-κB response (Taguchi et al ., 2015). It also regulated the expression of MMPs.…”
Section: The Inhibition Of Plant Constituents Against In Vivo Animal mentioning
confidence: 99%
“…In addition, both 5-O-caffeoylquinic acid and 3-O-caffeoylquinic acid were also reported to have an in vitro liver protective effect against carbon tetrachloride (CCl 4 ) challenges. 20 Sakuranetin is a avonoid that has been previously reported to have antioxidant 21 and anti-inammatory effects, [21][22][23] which may contribute to the in vitro antiinammatory effect of Xeniji. 9 The presence of these polyphenols contributed to the antioxidant effect of Xeniji 10 and provided evidence that Xeniji may possess a hepato-recovery effect.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that sakuranetin possesses anti-inammatory effects by inhibiting the NF-kB pathway. 21 The anti-inammatory effect of the phenolic acids of Xeniji helps to prevent the formation of reactive peroxynitrite and TNF-a, which induce apoptosis of hepatic cells.…”
mentioning
confidence: 99%